In love and war: The morphometric and phylogenetic basis of ornamentation, and the evolution of male display behavior, in the livebearer genus Poecilia. (1st February 2019) - Goldberg, Daniel L.; Landy, Joseph A.; Travis, Joseph; Springer, Mark S.; Reznick, David N.
Abstract: Exaggerated male traits under sexual selection are often used for both competition and courtship, raising the question of whether ornaments evolved simultaneously for both functions, or if use in one context preceded use in another. Here, we apply a phylogenetic approach to study the evolution of ornamental dorsal fins in male poeciliid fish of the subgenera Mollienesia and Limia, which exhibit convergent development of an enlarged dorsal fin, and often direct erect‐fin displays to male and female conspecifics. Unlike prior categorical assessments of poeciliid adornments, we measure dorsal fin exaggeration with a continuous index of ornamentation. Phylogenetic logistic and generalized least squares regression analyses indicate that high index values are significantly associated with the use of two component postures of courtship and aggressive displays, dorsal fin erection and body curvature, but not with the presence of sexual dichromatism. Male displays initially evolved for male–male aggression in the common ancestor of Mollienesia and Limia, suggesting that this signal originated for competition, then became co‐opted for courtship. These results support the armament‐ornament hypothesis for evolution of exaggerated male traits, and are consistent with an evolutionary shift in the predominant mechanisms of sexual selection from intra‐ to intersexual.